Cultural Agenda Setting: Media Attributes and Public Attention of Greek Museums - Bantimaroudis, Philemon; Zyglidopoulos, Stelios C.; Symeou, Pavlos C.; Bantimaroudis, Philemon; Zyglidopoulos, Stelios C. (My University, 2012)
The recent transformation of cultural organizations has altered their relationship with the public, evidenced by their engaging in market research and analysis of public perceptions about their identity, mission, and services. Through the lens of agenda-setting theory, this paper examines whether, alongside other factors, media coverage of museums can drive museum visitation. We pursue a second level of agenda-setting analysis, examining the relationship between valence-the positive, negative and neutral portrayals of museums in the media-and visitation. We conduct an econometric analysis of monthly data for the period June 2004-June 2008 for a sample of major Greek museums. The study reveals that media coverage of cultural organizations and positive valence constitute significant elements of reputation, which subsequently drive museum visitation.
Keywords: Museums; Museum visitors; Research; Public opinion; Open access publishing